2011
DOI: 10.4161/cbt.11.6.14414
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma B16-F1 cells coated with fusion protein of mouse calreticulin and virus G-protein coupled receptor induced the antitumor immune response in Balb/C mice

Abstract: In apoptotic progress of tumor cells stimulated by special agents, the calreticulin (CRT) was relocated from endoplasmic reticulum onto the cell surface. When used as cellular antigen to immunize experimental animals, these CRT-coated apoptotic tumor cells could initiate effective anti-tumor immunoresponse against homologous tumor cells, indicating the value of CRT in anti-tumor immunotherapy. In order to develop an universal technique that could make CRT-coating more efficiently in the tumor cells, in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Exogenously added CRT also potentiates the immunogenicity of melanomas in patients [43]. A CRT fusion-protein added to B16 cells evoked an antitumor immune response in mice [44]. Intriguingly, therapeutic intervention associated with upregulation of CRT involves the generation of reactive species [4547].…”
Section: Discussionmentioning
confidence: 99%
“…Exogenously added CRT also potentiates the immunogenicity of melanomas in patients [43]. A CRT fusion-protein added to B16 cells evoked an antitumor immune response in mice [44]. Intriguingly, therapeutic intervention associated with upregulation of CRT involves the generation of reactive species [4547].…”
Section: Discussionmentioning
confidence: 99%
“…Danger signaling-potentiating therapies have been recently shown to associate with favorable clinical outcome in cancer patients (5,12,13). Moreover, it has been proposed that, combinatorial therapy with exogenously supplied danger signals could hold great immunogenicity-promoting potential (14).…”
Section: Introductionmentioning
confidence: 99%
“…lines, a method that can easily coat CRT onto the surface of any tumour cell would aid in providing a potent research tool for antitumour immunotherapy. In our previous studies, we used a B16-F1 mouse melanoma cell line coated with mCRT-vGPCR as a whole-cell tumour vaccine to immunise experimental animals and found that this whole-cell vaccine could induce a strong antitumour effect against the homologous tumour (18). In this study, we further evaluated the immune responses induced by this mCRT-vGPCR-coated whole-cell vaccine both in vivo and in vitro.…”
Section: Whole-cell Vaccine Coated With Recombinant Calreticulin Enhamentioning
confidence: 98%